Pemenuhan Hierarki Kebutuhan Tokoh Dasiyah dalam Novel Gadis Kretek Karya Ratih Kumala - Kurniawan, Ovie Sandy; Zahro, Azizatuz (Widyantara, 2025)
Penelitian ini mengkaji tokoh Dasiyah melalui pendekatan psikologi sastra dengan fokus pada perkembangan jiwanya. Tujuannya adalah mendeskripsikan bentuk pemenuhan dan hambatan yang dihadapi Dasiyah dalam memenuhi kebutuhannya sejak kecil hingga dewasa. Kajian ini menggunakan teori hierarki kebutuhan Abraham Maslow yang meliputi lima tingkatan: kebutuhan fisiologis, rasa aman, cinta, penghargaan, dan aktualisasi diri. Metode yang digunakan adalah kualitatif deskriptif, dengan data dikumpulkan melalui studi dokumentasi dan pembacaan mendalam novel. Hasil penelitian menunjukkan bahwa Dasiyah menghadapi berbagai hambatan, namun tetap berjuang memenuhi kebutuhannya secara bertahap sesuai teori Maslow. Ia menunjukkan semangat dan ketekunan untuk berkembang hingga mencapai aktualisasi diri. Penelitian ini memberikan gambaran bahwa karakter dalam karya sastra bisa merefleksikan proses pertumbuhan pribadi dan motivasi manusia untuk terus maju, meskipun menghadapi berbagai tantangan dalam hidup. The novel Gadis Kretek tells about the family life of the owner of a famous home-based kretekfactory in the city of M. The novel also tells about the history of the kretek factory industry, kretek business competition, and the romantic life experienced by the characters. This research uses literary psychology studies with a focus on the complex character of Dasiyah as a key character who reflects her psychological development. The purpose of this research is to describe Dasiyah's form and obstacles in fulfilling her needs from birth to adulthood. The approach used is humanistic psychology based on Abraham Maslow's theory of the hierarchy of needs, which consists of five levels: physiological, safety, love, esteem, and self-actualization.The research method used is descriptive qualitative, with data collection through documentary studies and in-depth reading of the novel. The result of the research is a description of the fulfillment of Dasiyah's hierarchy of needs and the obstacles she faces, presented in Maslow's order. The results show that human beings have the motivation to continue to develop in spite of various obstacles. Dasiyah shows perseverance in overcoming obstacles and is determined to achieve self-actualization. Dasiyah continues to develop according to her competence, regardless of the obstacles she encounters. She continues to rise and has the motivation to live until she is able to become a full human being. This research provides insight into how characters in literature can reflect efforts to fulfill needs and personal growth.